Fiscal activism in the euro area and in other advanced economies: New evidence - Maria Grazia Attinasi; Alessandra Anna Palazzo; Beatrice Pierluigi (European Central Bank (ECB), 2019)
We review the determinants of the discretionary fiscal policy action of governments in the euro area and in other advanced economies during the past 20 years. This is done by estimating fiscal reaction functions using dynamic panel techniques and country-by-country estimates. The results suggest that, on average, discretionary fiscal policy did not deliver economic stabilisation: during good economic times (positive output gaps) it has been on average pro-cyclical both in the euro area and in the other regions. However, the loosening bias during good times has been countered by the presence of efficient public institutions, higher long term interest rates and higher debt-to-GDP ratios. Overall, as a result of various counterbalancing forces, fiscal activism has not been a major feature of policy making in the euro area, nor in other advanced economies during the past 20 years.
Keywords: E62; H6; C23; 330; fiscal stance; business cycle; government effectiveness; panel estimates